2013
DOI: 10.1186/1756-3305-6-61
|View full text |Cite
|
Sign up to set email alerts
|

Abundance, behavior and entomological inoculation rates of anthropophilic anophelines from a primary Colombian malaria endemic area

Abstract: BackgroundIn Colombia for several years, the Urabá-Bajo Cauca and Alto Sinú region has registered the highest numbers of malaria cases in the country. Malaria vector incrimination and the characterization of entomological parameters will allow for a better understanding of malaria transmission dynamics and the design of effective vector control strategies for this region.MethodsWe conducted a longitudinal survey between November 2008 and June 2010 to quantify entomological (abundance and biting activity) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
76
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(92 citation statements)
references
References 62 publications
9
76
1
6
Order By: Relevance
“…In seven of the nine locations sampled during March and May, 2015, A. nuneztovari mosquitoes were present except in El Rayo-TAZ (Antioquia) and San Francisco de Tauchigadó-MAT (Chocó). Similarly, other studies have found A. nuneztovari in some locations of Antioquia and Chocó (6,7,11,16,26). Interestingly, the last report of A. nuneztovari in Chocó dates from 2004 (26), which evidences the importance of continuously listing malaria vectors present in the different regions of Colombia and keeping updated information for vector control strategies.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…In seven of the nine locations sampled during March and May, 2015, A. nuneztovari mosquitoes were present except in El Rayo-TAZ (Antioquia) and San Francisco de Tauchigadó-MAT (Chocó). Similarly, other studies have found A. nuneztovari in some locations of Antioquia and Chocó (6,7,11,16,26). Interestingly, the last report of A. nuneztovari in Chocó dates from 2004 (26), which evidences the importance of continuously listing malaria vectors present in the different regions of Colombia and keeping updated information for vector control strategies.…”
Section: Discussionmentioning
confidence: 58%
“…In this study we analyzed species abundance and composition, biting preferences and natural infection with Plasmodium of Anopheles mosquitoes from nine locations of two malaria-endemic regions of Colombia. Results showed a predominance of A. nuneztovari mosquitoes (53.5%), followed by A. darlingi (34.5%), known as the main malaria vectors in the country (5)(6)(7)16). In seven of the nine locations sampled during March and May, 2015, A. nuneztovari mosquitoes were present except in El Rayo-TAZ (Antioquia) and San Francisco de Tauchigadó-MAT (Chocó).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations